Aspects of ethics in four plays by Hélène Cixous - Williams, Martina (2012)
This thesis examines ethical questions in four plays written by Hélène Cixous for the Théâtre du Soleil; L'Histoire terrible mais inachevée de Norodom Sihanouk, roi du Cambodge (1985), L'Indiade ou L'Inde de leurs rêves (1987), La Ville parjure ou le Réveil des Erinyes (1994), and Tambours sur la digue (1999). It begins by establishing a working definition of the remit of ethics and discussing some of Cixous's accounts of writing for the theatre. It goes on to compare the use of power by three different groups in Norodom, suggesting how power may be used ethically. There is an examination of how identity is created in Indiade, which leads to analyses of the ethical value of love and of innocence. Three conflicting models of justice are identified in Ville parjure, and there is an exploration of the question of what the basis of justice should be. The ethical implications of the manipulation of the dramatic form of tragedy in Tambours are then discussed. In the final chapter of the thesis, the responses to these apparently disparate questions are brought together. Drawing on the conclusions of the previous chapters, the final chapter suggests answers to the questions of 'where can ethical questions be asked?', 'what should the basis of ethics be?', and 'whom should I care about?'.